Design of hierarchical double-layer NiCo/NiMn-layered double hydroxide nanosheet arrays on Ni foam as electrodes for supercapacitors. (August 2021) - Chen, X.; He, M.; Zhou, Y.; He, G.; Meng, C.; Cheng, Q.; Li, F.
Abstract: Reasonably designing the structure of composite materials and effectively increasing electroactive sites of electrode materials are considered as the promising approaches to enhance the electrochemical performance for supercapacitors. Herein, a double-layer layered double hydroxide nanosheet array grown on Ni foams is constructed through a facile two-step hydrothermal method. The as-prepared double-layer electrode materials including Ni, Co, and Mn elements possess large surface area and porosity; thus, it can increase the contact between electrolytes and the electrode materials, which leads to an increase in electroactive sites and high electrochemical performance. The double-layer electrode shows a high capacitance performance (2950 F/g at 1 A/g) and superior cycling stability (79% retention after 10, 000 cycles at 10 A/g). In addition, the asymmetric NiCo/NiMn-LDHs//AC device is fabricated and manifests good capacity with excellent cyclic stability of 82.2% after 10, 000 cycles. Highlights: Double-layer NiCo/NiMn-layered double hydroxide (LDH) nanosheet arrays grown on Ni foams are designed and constructed. The double-layer LDHs with abundant mesoporous and macroporous feature improve the contact between electrolytes and electrode materials. NiCo/NiMn-LDH composites show a high capacitance performance of 2950 F/g at 1 A/g.